Collaborative Journalism from a Latin American Perspective: An Empirical Analysis - Lucia Mesquita; Mathias-Felipe de-Lima-Santos (Journalism and Media, 2021)
The practice of collaboration in journalism is not new. The developments in information and communication technologies (ICTs) are understood by many scholars as the critical factor for collaborative journalism to flourish across newsrooms. By working together, practitioners can address the challenges of a profession in crisis as well as the need to produce quality investigative reporting. Much of the academic discussion regarding cooperative efforts in journalism has happened in the US and Europe. This paper aims to shed light on collaborative journalism outside this region, focusing on Latin America. To conduct our study, we looked at the literature concerning collaborative journalism in the Scopus and Scielo databases to build a survey that was shared among Latin American practitioners who worked on collaborative projects in recent years. Our findings show that Latin American news organisations are taking part or forming collaborative efforts to share a set of practices, processes, and motivations. However, their motivations are different from their Western counterparts, as Latin American journalists are looking for ways to fulfil the normative role of journalism in society and occupying spaces left by the mainstream media. By doing so, practitioners focus on topics and communities that are often misrepresented, forgotten, or underreported in the media. Finally, our paper concludes by suggesting a profile of news outlets working on collaborative projects across the region, and we provide some directions for future research.